1990
DOI: 10.1182/blood.v75.11.2143.2143
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal responses of myeloid progenitor cells to recombinant human colony-stimulating factors in congenital neutropenia

Abstract: The effects of recombinant human interleukin-3 (IL-3) and recombinant human granulocyte colony-stimulating factor (G-CSF) on the growth of myeloid progenitor cells (CFU-C) in semisolid agar culture were studied in two patients with Kostmann-type congenital neutropenia. CFU-C growth in bone marrow cells from patients was significantly reduced in response to various concentrations of either IL-3 or G-CSF alone, compared with that from normal subjects. There was no inhibitory effect of bone marrow cells from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Since G-CSF plays a crucial role in the stimulation of granulopoiesis (3,8), this cytokine has been widely used in the treatment of SCN (40). Although myeloid progenitor cells from SCN patients frequently show reduced responsiveness to G-CSF (41,42), treatment with pharmacological doses of G-CSF are able to restore the neutrophil count in the majority of SCN patients (33), leading to a concomitant reduction in infection-related events (33,(42)(43)(44). It has also been employed in other neutropenic conditions, including those associated with chemotherapy (45)(46)(47).…”
Section: G-csf Therapymentioning
confidence: 99%
“…Since G-CSF plays a crucial role in the stimulation of granulopoiesis (3,8), this cytokine has been widely used in the treatment of SCN (40). Although myeloid progenitor cells from SCN patients frequently show reduced responsiveness to G-CSF (41,42), treatment with pharmacological doses of G-CSF are able to restore the neutrophil count in the majority of SCN patients (33), leading to a concomitant reduction in infection-related events (33,(42)(43)(44). It has also been employed in other neutropenic conditions, including those associated with chemotherapy (45)(46)(47).…”
Section: G-csf Therapymentioning
confidence: 99%
“…S evere congenital neutropenia (SCN) 1 is a heterogeneous disease state characterized by a severe reduction in circulating neutrophils ( Ͻ 0.2 ϫ 10 9 /liter), and a maturation arrest of bone marrow progenitor cells at the promyelocyte/myeloid stage (1)(2)(3). Myeloid progenitor cells from SCN patients frequently show reduced responsiveness to G-CSF in vitro (4,5). Moreover, treatment with pharmacological doses of G-CSF is able to restore the neutrophil count in the majority of SCN patients (5)(6)(7).…”
mentioning
confidence: 99%
“…Although most patients with SCN respond to G‐CSF treatment, in order to induce a response many of them require considerably higher doses than is necessary in other neutropenic situations ( Imashuku et al , 1992 ; Dale et al , 1993 ). In vitro studies have also shown a relative resistance to G‐CSF of progenitor cells from SCN patients ( Kobayashi et al , 1990 ; Hestal et al , 1993 ) raising the possibility of a partial defect in the G‐CSF signal transduction pathway. Several groups have demonstrated that patients with SCN are able to produce normal or elevated levels of functionally normal G‐CSF ( Mempel et al , 1991 ; Pietsch et al , 1991 ; Bernhardt et al , 1993 ; Guba et al , 1994 ) and neutrophils from patients with SCN have also been shown to express normal numbers of G‐CSF receptors (G‐CSFR) with similar binding affinities to control cells ( Kyas et al , 1992 ).…”
mentioning
confidence: 99%